Microbes drive changes in arsenic species distribution during the landfill process. (1st January 2022) - Hu, Lifang; Zhang, Dongchen; Qian, Yating; Nie, Zhiyuan; Long, Yuyang; Shen, Dongsheng; Fang, Chengran; Yao, Jun
Abstract: Landfills are considered an anthropogenic source of arsenic (As). The As species mediated by microbes in landfills vary significantly in toxicity. Based on random matrix theory, 16S rRNA genes were used to construct four microbial networks associated with different stages over 12 years of landfill ages. The results indicated that network size and microbial structure varied with landfill age. According to the network scores, about 208 taxa were identified as putative keystones for the whole landfill; the majority of them were Firmicutes, which accounted for 66.8% of all specialists. Random Forest analysis was performed to predict the keystone taxa most responsible for As species distribution under different landfill conditions; 17, 10 and 14 keystone taxa were identified as drivers affecting As species distribution at early, middle, and later landfill stages, respectively. Highlights: About 208 taxa were identified as putative keystones for the whole landfill. Firmicutes accounted for 66.8% of all specialists. Keystone taxa were identified as drivers affecting As species at different landfill stage.